Patient experiences with and adherence to Crohn’s disease exclusion diet in Dutch Crohn’s disease patients: a cohort study - Fleur T. R. Wijers; Suzanne M. C. van Zundert; Charlotte M. Verburgt; Nikki van der Kruk; Johan E. Van Limbergen; Nicolette J. Wierdsma (Therapeutic Advances in Gastroenterology, 2025)
Background: Dietary therapy is commonly used as a treatment for Crohn’s disease (CD). High dietary adherence is associated with achieving clinical remission. Crohn’s disease exclusion diet (CDED) is a relatively new therapy in the management of CD. Objective: This publication aims to assess the first real-life patient experience with and adherence to Crohn’s disease exclusion diet plus partial enteral nutrition (CDED + PEN) in Dutch children and adults with mild-to-moderate CD. Design: Interviews were performed with patients and/or caregivers prospectively after phases I, II, and III, and once after finishing therapy in a retrospective cohort. Methods: We obtained data on patient experiences with CDED and the accompanying Modulife patient support platform and assessed effectiveness from patients’ and physicians’ perspectives based on medical and clinical data obtained from the patient file. The interview contained open questions, 5-point Likert scales, and Net Promotor Scores (NPS). Results: Sixty-nine patients were included (52 pediatric and 17 adults). Approximately half of the patients in the prospective cohort and the majority (83%) of patients in the retrospective cohort would recommend CDED to others. Two-thirds of the patients would reconsider starting CDED again. A positive NPS (31) was given for recommending the support platform to others with the recipes feature as the most used and esteemed part. Median fecal calprotectin and C-reactive protein gradually decreased from baseline to 18 weeks of therapy in both children and adults. Two-thirds of the physicians assessed the diet as showing good effectiveness and would continue the dietary therapy at each phase of the diet. Conclusion: Many mild-to-moderate active CD patients may experience positive outcomes and have good experiences with the CDED + PEN dietary therapy and the associated Modulife patient support platform. This study might add valuable patient perspectives to the growing clinical use of CDED in managing CD.